Migrations and the sacred topography of the Deliblato Sands: The village of Deliblato - Sorescu-Marinković, Annemarie; Živković, Valentina (Swedish Journal of Romanian Studies, 2026)
This paper focuses on the co-shaping of nature and the sacred landscape of the village of Deliblato, located on the margins of the Deliblato Sands, in Vojvodina, Serbia, also known as the “European Sahara”. This study illustrates how ‘natural’ and ‘cultural’ landscapes are inseparable, mutually shaped by human and non-human forces. We take two directions of research into how environmental reality impacts human-created sacred spaces: 1) we explore how migrations and cultural interactions, defining this area, constructed the sacred spaces on the margins of this specific landscape, and 2) we analyse how the landscape is represented and reflected in the sacred topography of the village of Deliblato. The object of our study is two rural Christian Orthodox churches – the Serbian and the Romanian, as well as the village cemetery, in which we investigated whether certain landscape features favoured the formation of certain types of religious or sacred representations.